GENERAL CONSIDERATIONS ON THE DISCIPLINARY LIABILITY OF ARCHITECTS - Andra PURAN; Alina MARINESCU; Ramona DUMINICĂ (Challenges of the Knowledge Society)
As well as other liberal professions in Romania, also the profession as an architect is regulated by special norms, the Law No 184/2001, whose provisions are amended by the Rules governing the functioning and organization of the Romanian Order of Architects and the Code of Ethics of Architects. The specificity of the disciplinary liability of the architects towards the common law is given by specific sanctions, by the authorities competent in performing the disciplinary investigation of the disciplinary offences, as well as by the specific procedural rules. The present study aims to offer a brief analysis of these aspects which differentiate the disciplinary liability of architects towards that of the employees performing their activities under an employment contract.